Characterization and failure analysis of plastics - Menna, Todd J. (ASM Handbook ;, 2022)
"Volume 11B serves as a reference and guide to help engineers determine the causes of failure in plastic components and make corrective adjustments through design and manufacturing modifications. It contains seven major divisions, covering polymer science and processing, material selection and design, chemical, thermal, and physical analysis, mechanical behavior and testing, degradation mechanisms, systematic failure analysis, and life assessment and optimization. It examines a wide range of factors that contribute to the properties and behaviors of engineering plastics and the effect of thermal and mechanical stresses, impact loading, fatigue, wear, weathering, moisture and chemical exposure, photochemical aging, microbial degradation, and elevated temperatures. It addresses issues such as flammability, environmental stress cracking, crazing, and stress whitening and describes the unique characteristics of polymer fracture and how to assess and predict service life using fracture mechanics. It also presents and analyzes numerous examples of failure, including design and manufacturing related failures, wear failures of reinforced plastics, and failures due to creep and yielding."--